Evaluation of the Sudanese Native Chicken Production System and Major Constraints (Journal of Veterinary Medicine and Animal Production, 2021)
The objective of this study was to assess the production system of the Sudanese native chicken kept under traditional conditions. The study was conducted in three different regions: namely Kordofan, Blue Nile and Gedaref. However within each region three to five districts were randomly selected and similarly two to five villages from every district were also considered. A total of 209 households were interviewed and a structured pre-tested questionnaire was administered to them. The statistical software SPSS was used to obtain descriptive statistics, while ANOVA and Duncan Multiple Range Test were applied for comparing and separating means among the surveyed regions, respectively. The study revealed that native chickens were predominantly raised under the extensive production system (98.4%). Among the livestock diversity kept by the households, chicken exhibited the lowest ranking priority. On the other hand women were classified as the highest contributors to chicken ownership, management and decision making within the families. The flock size and cock: hen ratio ranged from 25.4 to 37.0 and 1: 2.24 to 1: 3.34, respectively. The main purposes of native chicken keeping in this study were meat provision and cash generating. As indicated by respondents, prevalence of infectious diseases, predators and lack of veterinary services and heath care were considered to be the major constraints facing the Sudanese native chickens keeping under the extensive system.
Keywords: native chicken; production system; major constrains; Household Survey